Substitution of legume hays for cottonseed cake in rations based on corn crop residues for sheep under confinement - Oliveira, Ederlon R. de; Barros, Nelson N.; Robb, Thomas W.; Johnson, William L.; Pant, Kant P. (Pesquisa Agropecuaria Brasileira, 2014)
Two experiments utilizing hairy sheep were carried out to test the substitution of legume hays for cottonseed cake in rations based on com crop residues. In the first experiment, a basal ration of 51% corn crop residues, 28% cotton seed cake, 20% corn and 1% salt, was used, in which the cottonseed cake was replaced by 5%, 10%, and 15% of “mata-pasto" (Cassia sericea) hay, while a control group was kept under range conditions. The confined animals had gains of 95, 106,103 and 93 grams/head/day (P>0.05) for the rations with 0%, 5%, 10% and 15% of "mata-pasto", respectively. The grazing animals lost 11 grams/head/day, (P<0.05). In the second experiment, the cottonseed cake was either partially (50%) or totally replaced by "mata-pasto" or "cunhã" (Clitoria ternatea) hays, while the grazing sheep received a supplementation of 200 grams of corn grain/head/day. With the exception of the treatment in which the cottonseed cake was totally replaced by "mata-pasto" hay, the other treatments with confined animals showed gains above 100 grams/head/day, which were higher than (P<0.01) the 42 grams/head/day for the grazing animals. The results indicate that it is possible to substitute "mata-pasto" hay for cottonseed cake at levels up to 50%, while the total substitution can be made "cunhã" is used.